The New Inhibitor of Monoamine Oxidase, M30, has a Neuroprotective Effect Against Dexamethasone-Induced Brain Cell Apoptosis - Johnson, Shakevia; Ou, Xiao-Ming (Frontiers in Neuroscience, 2010)
Stress detrimentally affects the brain and body and can lead to or be accompanied by depression. Although stress and depression may contribute to each other, the exact molecular mechanism underlying the effects is unclear. However, there is a correlation between stress and an increase in glucocorticoid secretion which causes a subsequent increase in monoamine oxidase (MAO) activity during stress. Consequently, MAO inhibitors have been used as traditional antidepressant drugs. Cellular treatment with the synthetic glucocorticoid, dexamethasone (a cellular stressor), has been reported to markedly increase both MAO A and MAO B catalytic activities, as well as apoptosis. This study compares the neuroprotective abilities of M30 (a new generation inhibitor of both MAO A and MAO B) with rasagiline (Azilect®, another new MAO B inhibitor) and selegiline (Deprenyl®, a traditional MAO B inhibitor) in the prevention of dexamethasone-induced brain cell death and MAO activity in human neuroblastoma cells, SH-SY5Y. M30 demonstrated the highest inhibitory effect on MAO A; however, M30 showed the lowest inhibitory effect on MAO B enzymatic activity in comparison to rasagiline and selegiline. Although, M30 exhibited the greatest neuroprotective effect by decreasing cell death rates and apoptotic DNA damage compared to rasagiline and selegiline, these neuroprotective effects of M30 were, overall, similar to rasagiline. Summarily, M30 has a generally greater impact on neuroprotection than the MAO B inhibitors, selegiline and rasagiline. Our results suggest that M30 may have great potential in alleviating disorders involving increases in both MAO A and MAO B, such as stress-induced disorders.